Geometry and topology of microscopic ribbons - Cheong, Kyra Kay Yen (Nanyang Technological University, 2022)
With a focus on the organic molecule that every living organism contains, this report strives to characterise the mechanical properties of DNA. For a contour length that far exceeds the thickness or diameter of a chain, the geometrical and topological configurations can be described by simplified models. Starting with the discrete freely jointed chain (FJC) model, the qualitative explanation provided a stepping stone for the development into the continuous limit of the worm-like chain (WLC). The applicability of these models, especially the latter, has demonstrated the ability to accurately predict the behaviour of organic polymers in stretching and twisting experiments conducted by researchers since the 70s.